Contacts between poultry farms, their spatial dimension and their relevance for avian influenza preparedness - Lena Fiebig; Timo Smieszek; Jennifer Saurina; Jan Hattendorf; Jakob Zinsstag (Geospatial Health, 2009)
Ongoing economic losses by and exposure of humans to highly pathogenic avian influenza (HPAI) in poultry flocks across Asia and parts of Africa and Europe motivate also outbreak-free countries such as Switzerland to invest in preparedness planning. Country-specific population data on between-farm contacts are required to anticipate probable patterns of pathogen spread. Information is scarce; in particular on how strongly small, non-commercial poultry farms are involved in between-farm contacts. We aimed to identify between-farm contacts of interest for HPAI spread at both commercial and non-commercial farms in a non-outbreak situation: whether or not commercial and non-commercial farms were involved in poultry and person movements and shared resources by company integration. Focus was on poultry movements for the purpose of purchase, sale and poultry show visits, their spatial dimension, their frequencies and the farm types they connected. Of the total 49,437 recorded poultry farms in Switzerland, 95% had less than 500 birds. The farm number resulted in densities of up to 8 poultry farms per km2 and a median number of 47 neighbour farms within a 3 km radius around the farms. Person movements and shared resources were identified in 78% of the surveyed farms (93% among commercials, 67% among non-commercials). Poultry trading movements over extensive spatial ranges were stated at 65% (79% among commercials, 55% among non-commercials). Movement frequencies depended on farm specialization and were higher for commercial than for non-commercial farms except for poultry show visits. Estimates however for the entire population revealed 3.5 times higher chances of a poultry purchase, and 14.6 times higher chances of exhibiting birds at poultry shows occurring in a given time by a farm smaller than 500 birds (non-commercial farm) than by a larger (commercial) farm. These findings indicate that both commercial and non-commercial farms are involved in neighbourhood and remote between-farm contacts relevant to HPAI spread. It is necessary to include all poultry farms, irrespective of their size and purpose in both livestock registration and disease surveillance systems, as well as in transmission models for poultry and zoonotic diseases.